A benchmarking of operational efficiency in Asia Pacific International cargo airports - Chung, Tae-won (2015)
This paper compares operational efficiency of major cargo airports in the Asia Pacific region. The multi-dimensional scaling cluster analysis by R-square method was used as the benchmarking tool to provide airport management with a means to examine various aspects of their operational efficiency against those of other airports. Ten operational efficiency factors for the clustering and efficiency estimation of airports in the Asia Pacific region were used in a regression model to overcome the complexity of multi-dimensional scaling approach. The resulting classification is used to identify the efficiency benchmarks of leading air cargo airports which have implications for Incheon airport in Korea.